Medical Spanish in U.S. Colleges and Schools of Pharmacy - Geoffrey A Mospan; Carrie L Griffiths (University of Minnesota Libraries Publishing, 2016)
Objective: To determine characteristics of Medical Spanish education provided to pharmacy students in schools and colleges of pharmacy in the United States. Methods: A survey of U.S. pharmacy schools and colleges was performed to determine availability of Medical Spanish in pharmacy curriculum, course(s) containing Medical Spanish education, and characteristics of Medical Spanish courses. Additional follow-up questions were asked if a school did not offer Medical Spanish. Results: 61 out of 138 institutions completed the survey (response rate = 44%). 36% (22/61) of respondents reported Medical Spanish education was offered in their curriculum. The most common barrier to offering a Medical Spanish course included a lack of personnel to teach the course (n=21, 54%) or no room in the curriculum (n=15, 38%). Conclusion: While there is a limited number of institutions that provide Medical Spanish education to their pharmacy students, results of this survey provide a basic description of Medical Spanish education in schools and colleges of pharmacy in the United States. Data obtained from this survey can be used to refine or initiate Medical Spanish courses, including the teaching and assessment methods used. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties   Type: Original Research